POLICY ANALYSIS PP No. 55/2007 IN THE MANAGEMENT OF RELIGIOUS EDUCATION - Faridatun Nikmah; Devi Pramitha; Fantika Febri Puspitasari (Edukasi Islami : Jurnal Pendidikan Islam, 2020)
Implementation of religious education as an education that instills moral values and spiritual until now still raises problematic situations in the community. This is because religious education, especially Islamic education in schools in its implementation, still shows less social issues, such as at least an hour PAI subjects in school are only two hours of lessons a week and the appearance dilemma in the management of religious education. Although substantially religious education was included in the national education system, its management remains handled by the Ministry of Religion. This is under Government Regulation No. 55 of 2007 on Religious Education and Religious Education, which mandates that religious education is the responsibility of the Ministry of Religious.